1994
DOI: 10.2135/cropsci1994.0011183x003400020019x
|View full text |Cite
|
Sign up to set email alerts
|

Pollen‐Parent Effects on Protein Quality and Endosperm Modification of Quality Protein Maize

Abstract: Quality protein maize (Zea mays L.) (QPM) has protein of high nutritional value conferred by the opaque‐2 (o2) gene and vitreous endosperm because of numerous modifier genes. Superior protein quality is only expressed when endosperm tissue is homozygous recessive (o2o2). During QPM research and development, it is common to evaluate trials in which QPM genotypes randomly interpollinate. We do not know if protein quality determinations for entries in such trials are valid measures of what would be expressed in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Therefore, the selection for high-oil rapeseed would be more effective based on the photosynthetic activity of silique wall than based on the performance of maternal parent. It should be noted that xenia has a direct genetic effect on OC in many crops [11, 12, 46, 47], and is applied not only in genetic and physiological research but also in crop breeding and production. Similar to the case of corn and soybean, controlling the pollen source and considering xenia are required in both breeding programs and investigation of OC in rapeseed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the selection for high-oil rapeseed would be more effective based on the photosynthetic activity of silique wall than based on the performance of maternal parent. It should be noted that xenia has a direct genetic effect on OC in many crops [11, 12, 46, 47], and is applied not only in genetic and physiological research but also in crop breeding and production. Similar to the case of corn and soybean, controlling the pollen source and considering xenia are required in both breeding programs and investigation of OC in rapeseed.…”
Section: Discussionmentioning
confidence: 99%
“…In many crops pollen parents have a direct genetic influence (xenia effect) on F 1 seeds (Song et al 1991;Pixley and Bjarnason 1994;Letchworth and Lambert 1998). For example, there was xenia effect on the oil content of corn, and which was estimated to be 0.35 (Song et al 1991).…”
Section: Improved Materials and Methodsmentioning
confidence: 99%
“…Blocks were assigned as two replications per location. Due to the contamination of foreign pollen on the ear (xenia effect) that was observed during our 2010 pilot study and previously reported in other QPM studies (Hossain et al, 2008; Pixley and Bjarnason 1994), five (WE) or three (CS, AM) ears were randomly chosen for self pollination and harvested separately to mimic the effects of each hybrid planted in an isolated grower's field. At the WE and CS locations, all plots were hand harvested to obtain yield and composition data.…”
Section: Methodsmentioning
confidence: 99%